2012
DOI: 10.12681/mms.327
|View full text |Cite
|
Sign up to set email alerts
|

Alien species in the Mediterranean Sea by 2012. A contribution to the application of European Union’s Marine Strategy Framework Directive (MSFD). Part 2. Introduction trends and pathways

Abstract: More than 60 marine non-indigenous species (NIS) have been removed from previous lists and 84 species have been added, bringing the total to 986 alien species in the Mediterranean [775 in the eastern Mediterranean (EMED), 249 in the central Mediterranean (CMED), 190 in the Adriatic Sea (ADRIA) and 308 in the western Mediterranean (WMED)]. There were 48 new entries since 2011 which can be interpreted as approximately one new entry every two weeks. The number of alien species continues to increase, by 2-3 specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
405
0
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 485 publications
(423 citation statements)
references
References 102 publications
11
405
0
7
Order By: Relevance
“…Despite the low number of ornamental fish species released in Greece, the possibility of other ornamental fish being introduced and established into the wild, either intentionally or unintentionally, still remains. Moreover, given that a number of introduced species of Indo-Pacific origin, recently reported in the eastern Mediterranean, belong to species kept in aquarium (Zenetos et al, 2012), a number of released sub-tropical/thermophilic fish species could become established and spread to the warmer southern parts of the country at least.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the low number of ornamental fish species released in Greece, the possibility of other ornamental fish being introduced and established into the wild, either intentionally or unintentionally, still remains. Moreover, given that a number of introduced species of Indo-Pacific origin, recently reported in the eastern Mediterranean, belong to species kept in aquarium (Zenetos et al, 2012), a number of released sub-tropical/thermophilic fish species could become established and spread to the warmer southern parts of the country at least.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in the Mediterranean Sea confirmed this pattern, both in terms of observations (Galil, 2008;Zenetos et al, 2012) and future projections (Ben Rais Lasram et al, 2010;Albouy et al, 2012).…”
Section: Introductionmentioning
confidence: 53%
“…At present, the number of macroalgal NIS reported in Venice Lagoon is 35, ca. 67% of the total number of alien macrophytes (52 taxa, Zenetos et al, 2012) recorded in the entire Adriatic Sea.…”
Section: Discussionmentioning
confidence: 99%
“…The latest lists of alien species in the Mediterranean Sea (Zenetos et al, 2010(Zenetos et al, , 2012 place this region amongst the most affected by biological invasions. In December 2010, the inventory of marine non indigenous species (NIS) included 955 taxa (except phytoplankton).…”
Section: Introductionmentioning
confidence: 99%